In situ electron microscopy of the self-assembly of single-stranded DNA-functionalized Au nanoparticles in aqueous solution. Issue 1 (7th December 2018) - Sutter, Eli; Zhang, Bo; Sutter, Stephan; Sutter, Peter
Abstract : In situ liquid cell electron microscopy of the pH-driven assembly of single stranded DNA-functionalized Au nanoparticles in aqueous solution. Abstract : Solution-phase self-assembly of DNA-functionalized nanoparticles into mesoscale structures is a promising strategy for creating functional materials from nanocrystal building blocks. The predominant approach has been the use of Watson–Crick base pairing between complementary bases in designated 'sticky ends' to trigger programmable self-assembly into ordered superlattices. Here we demonstrate the ordered self-assembly of Au nanoparticles conjugated with single-stranded (ss) DNA in acidic solutions. Au nanoparticles functionalized with thiolated ssDNA are protected against coalescence and the DNA conformation undergoes significant modifications at low pH, which can be associated with the protonation of adenine bases and the formation of a parallel poly-adenine duplex, which govern the interaction between ssDNA–Au nanoparticle conjugates. In situ liquid cell electron microscopy enables real-time imaging of the self-assembly process and the identification of key characteristics, such as the preferred structural motifs and interparticle separations in the native solution environment. Our results highlight alternatives to conventional base-pairing interactions for building DNA-directed nanoparticle superlattices.